Stydy on resistivity and micostructure of magnetron sputtered α-C:Si films - Onoprienko, A.A.; Yanchuk, I.B. (Functional Materials, 2006)
Electric resistivity and microstructure of silicon-doped (5 to 38 at. % Si) amorphous carbon (α-C) films deposited by de magnetron sputtering in argon plasma of composed (graphite + single crystalline silicon) target has been studied as a function of silicon content in films. The film resistivity parallel and perpendicular to substrate surface was measured. The film structure was studied by electron diffraction and Raman spectroscopy. Doping with silicon did not influence the resistivity p⊥ over the whole range of silicon concentrations studied, but resulted in marked increase in resistivity p║. Incorporation of silicon atoms into graphite-like cluster structure of carbon films results in distortion and disordering thereof in planes parallel to the substrate surface, thus promoting an increase in p║.